126k views
1 vote
Find the property of this : 5x*(4y+3x)=5x*(3+4y)

User Tsap
by
5.0k points

2 Answers

4 votes

Answer:

0

Explanation:

5x • (3x + 4y) - 5x • (4y + 3) =

User Gkpo
by
4.9k points
4 votes
Simplifying
5x(4y + 3x) = 5x(3x + 4y)

Reorder the terms:
5x(3x + 4y) = 5x(3x + 4y)
(3x * 5x + 4y * 5x) = 5x(3x + 4y)

Reorder the terms:
(20xy + 15x2) = 5x(3x + 4y)
(20xy + 15x2) = 5x(3x + 4y)
20xy + 15x2 = (3x * 5x + 4y * 5x)

Reorder the terms:
20xy + 15x2 = (20xy + 15x2)
20xy + 15x2 = (20xy + 15x2)

Add '-20xy' to each side of the equation.
20xy + -20xy + 15x2 = 20xy + -20xy + 15x2

Combine like terms: 20xy + -20xy = 0
0 + 15x2 = 20xy + -20xy + 15x2
15x2 = 20xy + -20xy + 15x2

Combine like terms: 20xy + -20xy = 0
15x2 = 0 + 15x2
15x2 = 15x2

Add '-15x2' to each side of the equation.
15x2 + -15x2 = 15x2 + -15x2

Combine like terms: 15x2 + -15x2 = 0
0 = 15x2 + -15x2

Combine like terms: 15x2 + -15x2 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.
User VDN
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.